Evaluation of the practical office advance (POA) training program using the kirkpatrick model - Muhammad Nurul; Rahmiati Rahmiati; Waskito Waskito; Yasdinul Huda (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to evaluate the effectiveness of the Practical Office Advance (POA) training program at BLK Pasaman Barat using the Kirkpatrick Model, with a focus on the gap between competency improvement and employment outcomes. A quantitative evaluation research design was applied involving 16 trainees selected through total sampling. Data were collected using validated questionnaires, pre-test and post-test, performance checklists, supervisor interviews, and documentation, and analyzed using descriptive statistics, paired comparison, and N-Gain. The results showed significant improvements in knowledge (33.54 to 74.38) and skills (30.62 to 85.43), with most participants achieving moderate to high N-Gain. However, behavioral transfer was moderate, and only 31% of participants obtained relevant employment. In conclusion, the POA training effectively improves technical competencies but has limited impact on employment outcomes, indicating the need to strengthen industry linkages and align training with labor market demands.